Canadian surveillance study of complex regional pain syndrome in children. Issue 6 (13th June 2022) - Baerg, Krista; Tupper, Susan M.; Chu, Luan Manh; Cooke, Nicole; Dick, Bruce D.; Doré-Bergeron, Marie-Joëlle; Findlay, Sheri; Ingelmo, Pablo M.; Lamontagne, Christine; Mesaroli, Giulia; Oberlander, Tim F.; Poolacherla, Raju; et al.
Abstract : Minimum pediatric incidence, diagnostic interventions, and treatments recommended by pediatricians and pain specialists for 168 cases of pediatric complex regional pain syndrome are reported. Abstract: This study describes the minimum incidence of pediatric complex regional pain syndrome (CRPS), clinical features, and treatments recommended by pediatricians and pain clinics in Canada. Participants in the Canadian Paediatric Surveillance Program reported new cases of CRPS aged 2 to 18 years monthly and completed a detailed case reporting questionnaire from September 2017 to August 2019. Descriptive analysis was completed, and the annual incidence of CRPS by sex and age groupings was estimated. A total of 198 cases were reported to the Canadian Paediatric Surveillance Program, and 168 (84.8%) met the case definition. The minimum Canadian incidence of CRPS is estimated at 1.14/100, 000 (95% confidence interval 0.93-1.35/100, 000) children per year. Incidence was highest among girls 12 years and older (3.10, 95% confidence interval 2.76-3.44/100, 000). The mean age of CRPS diagnosis was 12.2 years (SD = 2.4), with the mean time from symptom onset to diagnosis of 5.6 months (SD = 9.9) and no known inciting event for 19.6% of cases. Most cases had lower limb involvement (79.8%). Nonsteroidal anti-inflammatory drugs (82.7%) and acetaminophen (66.0%) were prescribed more commonly than antiepileptic drugs (52.3%) and antidepressants (32.0%). Referrals most commonly included physical therapy (83.3%) and multidisciplinary pain clinics (72.6%); a small number of patients withdrew from treatment because of pain exacerbation (5.3%). Pain education was recommended for only 65.6% of cases. Treatment variability highlights the need for empiric data to support treatment of pediatric CRPS and development of treatment consensus guidelines.